2020
DOI: 10.1080/14614103.2020.1718852
|View full text |Cite
|
Sign up to set email alerts
|

Isotopic Evidence for Changes in Cereal Production Strategies in Iron Age and Roman Britain

Abstract: Following the Roman conquest, agricultural production in Britain faced increasing demand from large urban and military populations. While it has long been thought that this necessitated an increase in agricultural production, direct archaeological evidence for changes in cultivation practices has been scarce. Using a model that conceptualises cereal farming strategies in terms of intensive or extensive practices, this paper is the first study to address this question using carbon and nitrogen stable isotope da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
3
10
0
Order By: Relevance
“…Direct evidence for crop rotation is currently limited. Isotopic analysis of emmer, spelt and barley remains from Iron Age and Roman Stanwick, Northamptonshire, showed no statistical difference in the δ 15 N or δ 13 C (beyond the barley-wheat offset) values for the Iron Age or Roman period (Lodwick et al, 2021). Either they were grown in rotation from the Iron Age, or no move towards rotation of these crops in different fields took place.…”
Section: Aspects Of the Agricultural Revolution 2: Rotationmentioning
confidence: 92%
See 3 more Smart Citations
“…Direct evidence for crop rotation is currently limited. Isotopic analysis of emmer, spelt and barley remains from Iron Age and Roman Stanwick, Northamptonshire, showed no statistical difference in the δ 15 N or δ 13 C (beyond the barley-wheat offset) values for the Iron Age or Roman period (Lodwick et al, 2021). Either they were grown in rotation from the Iron Age, or no move towards rotation of these crops in different fields took place.…”
Section: Aspects Of the Agricultural Revolution 2: Rotationmentioning
confidence: 92%
“…The late Roman innovations proposed by Jones (1981; have, however, largely fallen by the wayside. More generally, agricultural intensification continues to be identified in broader studies of the period, but with an intended meaning of higher overall production rather than shifts in crop husbandry practices per se (Lodwick et al, 2021).…”
Section: Cerealization: Conceptsmentioning
confidence: 99%
See 2 more Smart Citations
“…A close control of feeding times and foodstuffs, as well as keeping animals in stables or stys, are possible factors behind livestock size increase in the Roman period. However, some works have suggested that extensive agricultural practices were practised in different parts of the Roman Empire (MacKinnon 2001;Albarella et al 2019;Lodwick et al 2020). The extent to which agricultural practices were more or less intensive or extensive (in terms of inputs per unit area) might have varied greatly depending on various factors such as climate, soil, or demographic density, and understanding the particularities of this would require a multidisciplinary approach that is well beyond the scope of this paper.…”
Section: Environmental Factorsmentioning
confidence: 97%